2006
DOI: 10.1111/j.1365-2885.2006.00754.x
|View full text |Cite
|
Sign up to set email alerts
|

Critical review on the withdrawal period calculation for injection site residues

Abstract: This review concerns a statistical method for calculating withdrawal period for injection site residues. A recently adopted Committee for Medicinal Products for Veterinary Use/European Agency for the Evaluation of Medicinal Product (CVMP/EMEA) guideline recommends to apply the same method for the calculation of withdrawal period for injection site residues as for other edible tissues. For reasons in this study developed below, this approach is deemed to be inappropriate for the injection site residues. The inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…A historical example of this was the acute intoxication by clenbuterol shortly following consumption of veal liver or lamb and bovine meat in Europe (Pulce et al 1991;Salleras et al 1995;Sporano et al 1998;Barbosa et al 2005). For a product that is given by injection to food producing animals, acute manifestations of toxicity resulting from the ingestion of the entire injection site that contains high residues in a single meal is another possibility (Sanquer et al 2006a(Sanquer et al , 2006b. A further possibility is that people on a special occasion/event or a specific subpopulation may consume a large portion of food derived from an edible tissue where the veterinary drug residues may be more concentrated.…”
Section: Introductionmentioning
confidence: 99%
“…A historical example of this was the acute intoxication by clenbuterol shortly following consumption of veal liver or lamb and bovine meat in Europe (Pulce et al 1991;Salleras et al 1995;Sporano et al 1998;Barbosa et al 2005). For a product that is given by injection to food producing animals, acute manifestations of toxicity resulting from the ingestion of the entire injection site that contains high residues in a single meal is another possibility (Sanquer et al 2006a(Sanquer et al , 2006b. A further possibility is that people on a special occasion/event or a specific subpopulation may consume a large portion of food derived from an edible tissue where the veterinary drug residues may be more concentrated.…”
Section: Introductionmentioning
confidence: 99%
“…In the light of the depletion kinetics of veterinary drugs from injection sites, the calculation of withdrawal periods based on the concentrations of residues in injection site tissues demands special consideration. Recently, Sanquer et al (2006b) questioned the appropriateness of using a statistical methodology for calculating withdrawal periods from residues in injection site tissues and suggested alternative approaches. As the methodology used to calculate the withdrawal period may be critical to the conditions of use of injectable products in food-producing animals, a comprehensive review of the methodologies should be undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…A statistical approach involving a linear regression analysis to calculate withdrawal periods from the depletion of residues from injection sites has been described (EMEA CVMP, 1997, 2005b. However, Sanquer et al (2006b) reported that the assumptions for ensuring the validity of the linear regression analysis are not always satisfied while the assignment of withdrawal periods can involve extrapolations well beyond the range of the observed data -a practice that should be avoided. These workers concluded that the recommended statistical method is inappropriate for calculating withdrawal periods from residues in injection site tissues.…”
Section: Assigning a Withdrawal Periodmentioning
confidence: 99%
See 1 more Smart Citation
“…Some depot products have given rise to injection site residue concerns, as discussed in a recent review and in peer‐reviewed articles . The quantity of drug administered in most sustained release products is large, as it is required to provide an initially high and then well‐maintained therapeutic concentrations over two to five days.…”
Section: Formulationmentioning
confidence: 99%